1978
DOI: 10.1172/jci109037
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hypoxia on Myocardial Relaxation in Isometric Cat Papillary Muscle

Abstract: A B S T R A C T Myocardial relaxation is an important energy-dependent process. Hypoxia, unlike ischemia, has not been shown to impair myocardial relaxation. This difference may be because (a) the traditional index to assess isometric muscle relaxation (halftime to relaxation or RT,/2) reflects both changes in developed tension as well as relaxation and (b) the relaxation process is highly sensitive to temperature and previous papillary muscle studies have been conducted under hypothermic conditions. The prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

1979
1979
1992
1992

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Since ventricular relaxation involves the active uptake of calcium by the sarcoplasmic reticulum, it is not surprising that hypoxia or ischemia substantially may impair this process. 40 42 Indeed, Palacios and Powell43 and Frist et al 44 have presented strong evidence that hypoxia impairs the relaxation process of cardiac muscle both in the intact heart and the isolated papillary muscle preparation. Their studies did not permit assessment of the persistence of incomplete relaxation to end-diastole.…”
Section: Discussionmentioning
confidence: 99%
“…Since ventricular relaxation involves the active uptake of calcium by the sarcoplasmic reticulum, it is not surprising that hypoxia or ischemia substantially may impair this process. 40 42 Indeed, Palacios and Powell43 and Frist et al 44 have presented strong evidence that hypoxia impairs the relaxation process of cardiac muscle both in the intact heart and the isolated papillary muscle preparation. Their studies did not permit assessment of the persistence of incomplete relaxation to end-diastole.…”
Section: Discussionmentioning
confidence: 99%
“…However, their paper antedated the work of Serizawa et al (13) who considered the rate of ventricular relaxation as well as the extent of relaxation important in the analysis of hypoxia-induced diastolic effects. The review article also preceded the work of Frist et al (9) who showed that in isolated cat papillary muscle maintained at 38°C, relaxation time was increased rather than decreased during hypoxic conditions. Frist et al (9) pointed out that because conditions were maintained hypothermic in previous studies of hypoxic papillary muscle, a decreased rate of relaxation was not observed.…”
Section: Discussionmentioning
confidence: 77%
“…In terms ofSerizawa et al (13), the increased myocardial stiffness observed during hypoxia may be indicative ofincomplete or partial ventricular relaxation (see below). Ventricular relaxation has been shown to be a dynamic, energy dependent process (9,12,13,(32)(33)(34). When the energy supply to the heart muscle is decreased, the relaxation process may be altered such that increased ventricular resting tone occurs for a given end diastolic volume.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because different results concerning the effect of hypoxia on myocardial relaxation have been reported from studies conducted at different temperatures (16), we chose to perform this study at three temperatures. The left ventricle (LV)' becomes hypertrophied during senescence (6,8,(10)(11)(12)(13), and exercise conditioning alters cardiac function in hypertrophied hearts whether they are senescent or not (13,17).…”
Section: Introductionmentioning
confidence: 99%